0435 Pigeon breeding and the risk of interstitial lung disease, does number of pigeons matter?. (21st August 2017) - Cramer, Christine; Schlünssen, Vivi; Bendstrup, Elisabeth; Stokholm, Zara Ann; Vestergaard, Jesper Medom; Frydenberg, Morten; Kolstad, Henrik Albert
Abstract : Objective: We recently showed an increased risk of interstitial lung disease (ILD) among pigeon breeders. The current study aims to explore this finding further by investigating the relation between the duration and intensity of the pigeon exposure and the risk of ILD. Methods: This is a retrospective follow-up study from 1980 to 2013 of pigeon breeders identified in the records of the Danish Racing Pigeon Association. Since 2000 the association has kept annual records on the number of pigeon leg bands purchased by each breeder. From this information and the average pigeon life expectancy we will calculate number of pigeons kept. Dates of enrolment and resignation in the association are used to assess duration of pigeon breeding. Hospital based diagnoses of ILD are identified by linkage with the National Patient Registry 1977–2013. We will calculate hazard ratios with Cox regression analyses and censor participants at date of death, emigration, disappearance, diagnosis of connective tissue disease, or end of study by December 31 2013. Results: We have obtained information on number of pigeon leg bands and duration of membership for 2085 and 2656 pigeon breeders, respectively. Average number of pigeons kept is 132.73 per year and mean membership duration is 11.35 years. A total of 19 members are diagnosed with ILD. Statistical analyses are still pending but will be concluded before the conference, where results will be presented. Conclusion: This data provides a unique opportunity for investigating a possible exposure-response relation between pigeon related exposures and the risk of ILD.